Advances in Research on Isothermal Signal Amplification Mediated MicroRNA Detection of Clinical Samples: Application to Disease Diagnosis - Yu Han; Xin Sun; Sheng Cai (Biosensors)
With the rapid development of modern molecular biology, microRNA (miRNA) has been demonstrated to be closely associated with the occurrence and development of tumors and holds significant promise as a biomarker for the early detection, diagnosis, and treatment of cancer and other diseases. Therefore, detecting miRNA and analyzing it to determine its biological functions are of great significance for the screening and diagnosis of diseases. However, the intrinsic characteristics of miRNAs, including their low abundance, short sequence lengths, and high family-specific sequence homology, render traditional detection methods such as Northern blot hybridization, microarray use, and reverse transcription quantitative PCR (RT-qPCR) inadequate for meeting the stringent requirements of clinical detection in biological samples, a task requiring accuracy, rapidity, high detection power, specificity, and cost-effectiveness. In recent years, a substantial amount of effort has been put into developing innovative methodologies to address these challenges. In this review, we aim to provide a comprehensive overview of the recent advancements in these methodologies and their applications in clinical biological sample detection for disease diagnosis.